(3GdQMdI GdCfSjI aj GdQMdI GdbOSjIs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdZfi Yf YHOg GdabjQ GdPi jSQG ddg dg GdQMdI hGdeSjQ ef OeTb fTCJg Edi bOS MVQJg CeG HYO , ajbhd TjNfG GdTgjQ H GHf GdfGHdSi hgPg GdQMdI GdCfSjI Edi GdQMdI GdbOSjI s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3hNQLhG Edi RjGQJg hfRdhG YfOg ai OGNd Pdc GdecGf GdeHfi hNGQLg ai NjGege aEPG UOQ ef CMO TF ef GdeYGUi GdeNGdaI ddTQjYI hGdahGMT hEf cGf NajI de jXgQ s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eged GdfbW fGOQkG hai hGFdgG NQes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B473 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs